O ensino de ciências com agroecologia em uma abordagem interdisciplinar - Coelho, Fernando Antonio Oliveira (2021)
This text corresponds to the thesis from the following question, "Which Science teaching practices, interconnected with traditional knowledge and Agroecology, foment the development of interdisciplinary thinking in scientific knowledge?". The general objective of this inquiry is to analyze the critical capacity of students by Science teaching practices that allow them to develop interdisciplinary thinking. The thesis was based on foundations of interdisciplinarity and conceptual maps for meaningful learning. The research is qualitative in nature with field survey to understand the meanings and interpretations of the data obtained, and it was carried out in Productive Backyards and complemented into classrooms, with an interdisciplinary character between Science teaching, traditional knowledge and agroecological practices with active methodologies, where students moved from a condition of observers to researchers. In those practices, there was the exploration of Productive Backyards under different aspects such as perceptions and ways of understanding concepts and meanings. Field activities were complemented with deliberation and production of conceptual maps concerning the theme “Productive Backyard”. The methodological procedures took place in two stages: workshops with construction of conceptual maps and visits to Productive Backyards in two communities. A total of 48 7th grade students from two public schools, located in the rural area of the municipality of Bacabal, State of Maranhão, Brazil, were participants in this research. The instruments used to obtain data were personal notebooks, in which the students took notes during workshops and visits to the productive yards, in moments of discussion and negotiation of meanings and during conversation circles with yard owners. Conceptual maps made by the students themselves after two visits to the productive yards were also used for the data. The analysis of results was based on Meaningful Learning Theory, on development of interdisciplinary thinking about scientific knowledge and on the evolution of the students learning. In response to the guiding question of this research, it was revealed that a contextualized teaching of Science associated with the students' prior knowledge, traditional knowledge, concepts of Agroecology and natural phenomena present in Productive Backyards confirmed that the construction of scientific knowledge is manifested in a interdisciplinary way. The contextualized teaching of Science associated with the students' prior knowledge constitutes a pedagogical tool capable of motivating and arousing interest in a education of young people with scientific basis.